Hubungan Prokrastinasi dengan Stres pada Mahasisw Tingkat Akhir yang Sedang Menyusun Skripsi di STIKes Santa Elisabeth Medan Tahun 2021 - Fryska Yohana; Pomarida Simbolon; Maria Pujiastuti (Jurnal Indah Sains dan Klinis, 2022)
Students can never stay away from pressure. Stress is an unavoidable condition throughout everyday life and everyone has different feelings of anxiety. During the time of completing the thesis, students are faced with various obstacles, requests, and pressures. This is what causes students to prefer to procrastinate and it can be seen that student stress is influenced by the procrastination of the student. This research method uses an in-depth exploration configuration using a cross-sectional methodology. The example in this review was 62 respondents with the testing system, specifically basic arbitrary examining. The p-value of 0.001 (p < 0.05) indicates it that there is a relationship between indecision and student stress when composing a student proposal for the Nursing Study Program of STIKes Santa Elisabeth Medan 2021. They expected that students could motivate themselves to work on their thesis and manage their time so they don't experience problems, stress and no procrastination occurs.